Technical perspective: Node replication divides to conquer. - Harris, Tim (Communications of the ACM, 2018)
This article discusses the incorporation of concurrent data structures in computer operating systems and in-memory databases. The author comments on the use of node replication in automatically designing and building concurrent data structures. Other responsibilities for node replication processes, such as constructing replication and routing mechanisms, are also explored.